2020
DOI: 10.1111/papr.12943
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Psychological, Sleep, and Physical Activity Measures and Somatosensory Function in People With Peripheral Joint Pain: A Systematic Review and Meta‐Analysis

Abstract: Objective Alteration in somatosensory function has been linked to pain experience in individuals with joint pain. In this systematic review we aimed to establish the level of evidence of associations between psychological, social, physical activity, and sleep measures and somatosensory function that were assessed via quantitative sensory testing (QST) among individuals with joint pain. Methods A comprehensive literature search was conducted in 6 electronic databases from their inception to July 2019. Two revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 97 publications
5
8
0
2
Order By: Relevance
“…The reciprocal relationship between pain affecting sleep—and disturbances to sleep affecting pain—is well-established [ 2 , 3 , 4 , 5 , 9 , 10 , 11 ]. However, the PSQ-3 is the only PROM for directly assessing pain–sleep interactions in the CLBP population [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reciprocal relationship between pain affecting sleep—and disturbances to sleep affecting pain—is well-established [ 2 , 3 , 4 , 5 , 9 , 10 , 11 ]. However, the PSQ-3 is the only PROM for directly assessing pain–sleep interactions in the CLBP population [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The factors leading to chronic pain are complex, with multiple contributors leading to persistent symptoms [ 1 ]. Sleep quality and disturbances are one of the main contributors to chronic musculoskeletal pain [ 10 , 11 ]. The significant discriminative ability of the total PSQ-3-FI score to identify controls with no pain and the -ite and multisite chronic pain groups is in line with previous research that showed clear relationships between multisite pain and various sleep disturbances [ 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, effects of age must be considered when incorporating QST, as loss of sensory function has been observed in older adults for cold, warmth, mechanical, and vibratory detection thresholds ( 90 ). Moreover, a recent systematic review with meta-analysis surrounding the use of QST in individuals with joint pain, reports an association between depression, pain catastrophizing, and physical activity level with several QST measures; therefore, such variables need be acknowledged when evaluating the relationship between pain and somatosensory function ( 91 ). Despite the potential of such cofounding factors, the ability of QST to detect and discriminate peripheral vs. central contributors to pain, and its potential to help guide targeted therapies, including non-pharmacological interventions, argues for its greater incorporation in research and clinical initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Parecería ser que la ansiedad por sí misma es capaz de afectar la medida de los umbrales de presión medidos por algometría, disminuyéndolos. Othman en una revisión sistemática sobre alteraciones de la función somatosensorial en pacientes con dolor articular, encontró una significativa asociación de la ansiedad, la depresión y el catastrofismo con varias de las medidas de los TSC, ente ellos el UDP (14). Rudhi encontró que la ansiedad disminuye los umbrales de dolor y plantea que puede tener un rol en la determinación de hipersensibilidad central (15).…”
Section: Discussionunclassified